Extinguishing of Pool Fires using the Water Mist - Daniel Ondrusik; Dalibor Balner; Adam Thomitzek (Communications - Scientific letters of the University of Zilina, 2020)
Currently, there is progressive use of fire protection systems that use the high-pressure water mist. The extinguishing effect of water mist on flammable liquids is not sufficiently elucidated. Therefore, experiments were designed to gain new knowledge about the mechanism of the high-pressure water mist extinguishing.As a source of the pool fire, gasoline, kerosene, diesel and ethanol were used. Flammable liquids were stored in a circular steel container with a diameter of 165mm and a depth of 12mm. The container was placed in an enclosed room of 2.7 x 2.7m x 3m. In the experiment, the time to extinguish flammable liquids was measured using nozzles of different spray characteristics of the water mist. The nozzles with orifice 400 µm, 800 µm and 1000 µm were used at a constant pressure of 70 bar.